Resistensi Insulin sebagai Poros Disfungsi Ovulasi pada Polycystic Ovary Syndrome - Raymond R. Tjandrawinata (MEDICINUS, 2026)
Insulin resistance in polycystic ovary syndrome (PCOS) is intrinsic in nature and not merely a consequence of obesity. Postreceptorphosphorylation abnormalities, particularly excessive serine phosphorylation of the insulin receptor and insulin receptor substrate, impair the activation of PI3K/Akt pathway, resulting in compensatory hyperinsulinemia. This conditionstimulates CYP17A1 expression in ovarian theca cells, suppresses hepatic synthesis of sex hormone-binding globulin, and creates a hormonal milieu that disrupts follicular maturation, ultimately leading to oligo-anovulation. The improvementin ovulation reported with the use of glucagon-like peptide-1 (GLP-1) receptor agonists is better understood as an indirect consequence of systemic metabolic improvement. The bioactive fraction DLBS3233 acts at a more downstream level,restoring tyrosine phosphorylation and glucose transporter-4 (GLUT-4) expression by modulating peroxisome proliferatoractivated receptor (PPAR)-γ. Positioning insulin resistance as the central pathophysiological axis enables a more precisetherapeutic approach aligned with the physiological mechanisms underlying ovulatory dysfunction in PCOS.